Investigation of crystallized germanium thin films and germanium/silicon heterojunction devices for optoelectronic applications. (February 2015) - Lee, Won-Jae; Sharp, James; Umana-Membreno, Gilberto A.; Dell, John; Faraone, Lorenzo
Abstract: Crystallization of germanium (Ge) thin films was investigated by depositing Ge on glass and silicon substrates using electron beam (e-Beam) evaporation. The hole carrier concentration in Ge thin films deposited on glass substrates was found to decrease slightly with increasing annealing temperature, whereas its Hall mobility was found to increase monotonically. For all crystallized Ge thin films herein reported, the conductivity was found to be dominated by holes (p-type). This characteristic was then exploited to fabricate p-Ge/n-Si heterojunction diodes on n-type silicon substrates, which were then investigated by analysis of their current–voltage and capacitance–voltage characteristics. It was found that increasing annealing temperatures lead to significant improvements in on/off ratio and ideality factor, as well as increased built-in voltage. After crystallization of the top p-Ge layer through annealing at 600 °C, the devices indicated an on/off ratio of 10 6, an ideality factor of 1.25 and a built-in potential of 0.58 eV. The improvement in device performance is correlated with the crystallization of the Ge thin films, as confirmed by Hall effect and X-ray diffraction measurement, which indicated increases in hole mobility and improved solid-phase crystallization with increases in annealing temperature. The photoresponse of the devices was characterized employing a two-dimensional mapping approach, which provides insight into the optical generation and recombination processes at the Ge/Si heterojunction. The results herein presented indicate that thermally crystallized Ge thin films may be of significant promise for electronic and optoelectronic device applications.